ChemInform Abstract: Engaging Alkenyl Halides with Alkylsilicates via Photoredox Dual Catalysis. Issue 26 (June 2016) - Patel, Niki R.; Kelly, Christopher B.; Jouffroy, Matthieu; Molander, Gary A.
Abstract: Ammonium organobis(catecholato)silicates, serving as radical precursors, and alkenyl halides are cross‐coupled via dual photoredox/Ni catalysis.